THE PERCEPTIONS, ATTITUDES AND BEHAVIORS OF MOTHERS IN PROVIDING EARLY SEX EDUCATION - Fitri Erna Erfiany; Ahmad Suryawan; Nur Ainy Fardana Nawangsari; Ivon Diah Wittiarika (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground : Cases of child sexual abuse in Indonesia continue to increase. The need for a parent's role in providing sex education from an early age is expected to prevent children from sexual abuse. Savy Amira Women Crisis Centre mentions that Tambaksari sub-district has the highest crime rate in Surabaya. Perceptions, attitudes and behaviors of parents in the provision of sex education in early childhood can be described in PAUD Tunas Mandiri Pacar Keling Subdistrict Tambaksari Method: This research method is qualitative with phenomenological approach. The number of samples as many as 10 mothers with purposive sampling techniques. The variables studied were perception, attitude and behavior of the mother. Data is collected by indepth interview method and processed with Interactive Model Of Analysis. Result : Most respondents have a perception that sex education is behavior, but respondents know that sex education has a good purpose. This is reflected in the attitudes and behaviors shown by most respondents about how they provide sex education. All they've been doing is part of sex education, it's just that they don't know or realize that. The age, level of education and employment in this study had little effect on perceptions of providing sex education. Conclusion: Almost all mothers interpret the provision of sex education in early childhood is still a taboo thing to give, while for the attitude and behavior of the mother is shown by limiting the child and supervision when playing gadgets,introducing genitalia and teaching toilet training.